2021
DOI: 10.1186/s13015-021-00194-5
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing linear and branched evolution given single-cell DNA sequencing data of tumors

Abstract: Background Cancer arises from an evolutionary process where somatic mutations give rise to clonal expansions. Reconstructing this evolutionary process is useful for treatment decision-making as well as understanding evolutionary patterns across patients and cancer types. In particular, classifying a tumor’s evolutionary process as either linear or branched and understanding what cancer types and which patients have each of these trajectories could provide useful insights for both clinicians and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In the simulations performed by the author, ScisTree’s accuracy is similar to SCIPhI and SCITE, but it is much faster. Related approaches for single-cell SNV data include methods focused on cell clustering and clonal phylogeny [ 34 – 41 ], phylogenetic model selection [ 42 , 43 ], mutation ordering [ 44 ], genotype correction [ 45 ], or longitudinal comparisons [ 46 ]. Methods also exist for inferring phylogenies from single-cell copy number variants [ 47 ], but these are out of the scope of this study.…”
Section: Introductionmentioning
confidence: 99%
“…In the simulations performed by the author, ScisTree’s accuracy is similar to SCIPhI and SCITE, but it is much faster. Related approaches for single-cell SNV data include methods focused on cell clustering and clonal phylogeny [ 34 – 41 ], phylogenetic model selection [ 42 , 43 ], mutation ordering [ 44 ], genotype correction [ 45 ], or longitudinal comparisons [ 46 ]. Methods also exist for inferring phylogenies from single-cell copy number variants [ 47 ], but these are out of the scope of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Different bioinformatic approaches already exist for the calculation of clonal evolution of bulk sequencing data. In addition, the single cell sequencing method has expanded the field of reconstructing clonal evolution (14,(17)(18)(19). A study of Morita et al has shown both genetic and phenotypic evolution in AML by single cell sequencing and cell surface protein analyses (14).…”
Section: Introductionmentioning
confidence: 99%
“…Outside the above categories, Phyolin [40] and the method of [41] identify the mode of evolution given the binary genotype matrices obtained from single-cell SNVs. These methods, however, are aimed at distinguishing between linear and nonlinear modes (i.e., a binary classification), which is a simpler problem than the one we address here.…”
Section: Introductionmentioning
confidence: 99%